2020
DOI: 10.1212/wnl.0000000000010346
|View full text |Cite
|
Sign up to set email alerts
|

Serum neurofilament light as a biomarker in progressive multiple sclerosis

Abstract: There is an unmet need in multiple sclerosis (MS) therapy for treatments to stop progressive disability. The development of treatments may be accelerated if novel biomarkers are developed to overcome the limitations of traditional imaging outcomes revealed in early phase trials. In January 2019, the International Progressive Multiple Sclerosis Alliance convened a standing expert panel to consider potential tissue fluid biomarkers in MS in general and in progressive MS specifically. The panel focused their atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
125
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(130 citation statements)
references
References 45 publications
(80 reference statements)
3
125
2
Order By: Relevance
“…In primary progressive disease, reductions were seen following fingolimod [ 80 ] and ocrelizumab [ 78 ]. Given the lack of useful biomarkers otherwise for progressive types of MS, NfL is increasingly seen as an important secondary endpoint in phase 2 and 3 studies of treatments [ 81 ].…”
Section: Blood Nfl In Msmentioning
confidence: 99%
“…In primary progressive disease, reductions were seen following fingolimod [ 80 ] and ocrelizumab [ 78 ]. Given the lack of useful biomarkers otherwise for progressive types of MS, NfL is increasingly seen as an important secondary endpoint in phase 2 and 3 studies of treatments [ 81 ].…”
Section: Blood Nfl In Msmentioning
confidence: 99%
“…NfL is a marker of axonal loss and correlated significantly with inflammatory markers for MS activity, markers of neurodegeneration such as brain volume loss and therapeutic response (Kuhle et al., 2019). In our study, the course of the mean level of pNfL showed an increase at M3 and a slow decrease until M12, whereas the natural history of pNfL in the placebo groups of PMS shows stabilization or a regular increase over time (Kapoor et al., 2020). In addition, the course of the mean BV and CSCV was stable throughout the year.…”
Section: Discussionmentioning
confidence: 45%
“…Beyond imaging, other structural biomarkers are under development and validation in progressive MS. Neurofilament light chain (Nfl) is a novel marker that can be detected in serum or in cerebrospinal fluid with a good correlation between both measures ( 40 , 53 , 54 ). This non-specific biomarker serves as evidence of neuronal destruction and has a good correlation with MRI measures and possible with the risk of developing SPMS ( 25 , 55 , 56 ). However, technical methods for the analysis and Nfl concentrations in healthy subjects and at early phases of the disease should be addressed ( 56 ).…”
Section: Structural Markers To Identify Ms Progressionmentioning
confidence: 99%
“…This non-specific biomarker serves as evidence of neuronal destruction and has a good correlation with MRI measures and possible with the risk of developing SPMS ( 25 , 55 , 56 ). However, technical methods for the analysis and Nfl concentrations in healthy subjects and at early phases of the disease should be addressed ( 56 ). Future research should focus on the use of this biomarker for the monitoring of treatment response and disease progression.…”
Section: Structural Markers To Identify Ms Progressionmentioning
confidence: 99%